Effect of surgical rib fixation for rib fracture on mortality: A multicenter, propensity score matching analysis. Issue 3 (September 2019) - Shibahashi, Keita; Sugiyama, Kazuhiro; Okura, Yoshihiro; Hamabe, Yuichi
Abstract : BACKGROUND: Rib fracture is a common injury and can be associated with complications and a high mortality rate. There has been growing interest in surgical rib fixation as a treatment for rib fracture. However, results from previous studies are conflicting, and conclusive results regarding the efficacy of surgical rib fixation for rib fracture are lacking. This study aimed to investigate if surgical rib fixation improves prognosis in patients with traumatic rib fractures. METHODS: Using the Japan Trauma Data Bank, a nationwide trauma registry, we identified patients 18 years or older with rib fracture between 2004 and 2015. The primary outcome was in-hospital mortality. Logistic regression analysis was used to estimate a propensity score to predict reception of surgical rib fixation. We used a 1:4 propensity score matching analysis to compare patients who underwent surgical rib fixation with those who did not. RESULTS: Overall, 236, 698 patients were registered in the database, and 37, 571 were eligible for propensity score matching analysis. This analysis included 147 patients who underwent surgical rib fixation and 588 as controls. The in-hospital mortality rate was significantly lower in patients who underwent surgical rib fixation than in those who did not (4.8% vs. 16.2%, respectively; absolute difference: −11.4%; 95% confidence interval: −14.8% to −8.0%). CONCLUSION: This study showed that surgical fixation may reduce in-hospital mortality in patients with rib fracture. Surgical rib fixation may offer a better modality for the management of selected patients with rib fracture. LEVEL OF EVIDENCE: Therapeutic, level III.